Beyond Religiosity: Value, AI, and Perceived Ethicality Model for Predicting Customer Loyalty - Hendratmoko (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2026)
This study investigates whether perceived ethicality functions as the psychological mechanism through which AI-enabled banking services strengthen customer loyalty. Rather than relying on conventional demographic segmentation such as religion, ethnicity, or domicile, the study develops a value-oriented explanatory framework that emphasizes customers' ethical evaluations of banking services. A cross-sectional quantitative survey involving 270 banking customers from five major Indonesian cities was conducted. The proposed research model was evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM) implemented in SmartPLS 4.0. The empirical findings demonstrate that favorable evaluations of AI-enabled banking significantly enhance both perceived ethicality and customer loyalty. Furthermore, perceived ethicality exerts an independent positive influence on loyalty while simultaneously serving as a significant mediator between AI capability and customer loyalty. Practically, the findings suggest that banks should integrate AI capability with transparent and ethical service practices to strengthen long-term customer loyalty.